The thematic review on convective heat transfer of nanofluid over horizontal circular cylinder - Farahanie, Fauzi; Abdul Rahman, Mohd Kasim; Al-Sharifi, Hussein Ali Mohammed; Siti Farah Haryatie, Mohd Kanafiah (Akademi Baru, 2023)
Convective heat transfer refers to thermal energy transfer from one place to another due to the movement of fluid. To increase the performance of thermal energy transfer, nanoparticles are diluted into the fluid resulting nanofluid. Even though there are lots of studies have been conducted on the convection heat transfer of nanofluid, there are scarce studies that review the patterns of mainly used mathematical model, boundary conditions, surface geometry and method of solution. Therefore, this paper aims to review the studies on convective heat transfer of nanofluid over horizontal circular cylinder. The focus is to review published articles in the year 2014 until 2023. The reviewed articles were extracted using the advanced documents search function in SCOPUS and WOS databases. Of 67 identified articles, only 37 were selected after undergoing screening process. The result of this thematic review identifies that besides Buongiorno and Tiwari and Das models, mathematical models for non-Newtonian fluid like Viscoelastic, Casson, Jeffrey and Williamson models are also used in modeling convection heat transfer of nanofluid.